A pilot investigation of the impact of smoking cessation on biological age. (20th January 2017) - Lei, Man‐Kit; Beach, Steven R.H.; Dogan, Meeshanthini V.; Philibert, Robert A.
Abstract : Background and Objectives: Smoking is known to increase biological age. However, whether this process is reversible through smoking cessation is not known. In this pilot study, we attempt to determine whether smoking cessation reduces biological age. Methods: We conducted regression analyses of methylation data from 22 subjects, as they entered and exited inpatient substance use treatment, to determine change in biological age, as indicated by the deviation of their methylomic age from chronological age across two time points. Results: We found that, as compared to those subjects who did not stop smoking, subjects who significantly decreased their smoking consumption over a 1 month time period exhibited a marked reduction in methylomic age. Conclusion: The rapid and substantial reversal of accelerated aging associated with successful smoking cessation suggests that it can reverse well‐known smoking effects on methylomic aging. This preliminary finding can be readily examined in other, larger data sets, and if replicated, this observation may provide smokers with yet another good reason to quit smoking. Scientific Significance: Successful smoking cessation makes patients appear biologically younger than they were at baseline, and to do so quite rapidly. In today's youth driven society, our observations may serve as a powerful impetus for some to quit smoking. (Am J Addict 2017;26:129–135)